1987
DOI: 10.1007/bf00148972
|View full text |Cite
|
Sign up to set email alerts
|

Self-directed learning readiness and performance in the workplace

Abstract: Deep and rapid changes in a "high-tech" society exceed the ability of formal educational systems to respond to new learning needs. Therefore, the future of post secondary education will increasingly include emphases on self-directed learning skills and activities. Despite recognition of such a trend, knowledge of self-directed learning and self-directed learners is in its infancy.This study-of self-directed learning and performance was designed to determine the relationship of self-directed learning readiness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
88
0
8

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(175 citation statements)
references
References 5 publications
2
88
0
8
Order By: Relevance
“…Practitioners in the field of adult education hypothesize that self-directed learning develops over time (Guglielmino, Guglielmino & Long, 1987). Therefore, the length of the study period could have influenced the study results.…”
Section: Research Question 1: Does Reflective Practice Affect Readinementioning
confidence: 99%
“…Practitioners in the field of adult education hypothesize that self-directed learning develops over time (Guglielmino, Guglielmino & Long, 1987). Therefore, the length of the study period could have influenced the study results.…”
Section: Research Question 1: Does Reflective Practice Affect Readinementioning
confidence: 99%
“…Three quantitative studies have used the SDLRS to determine if differences in SDL readiness are related to differences in job performance. Guglielmino, Guglielmino, and Long (1987) studied 753 individuals ( 421 managers, 318 non-managers) from a large American utility company to determine if scores on the SDLRS were positively related to job performance in jobs that required either: (a) high levels of creativity and problem solving, (2) high levels of creativity, (3) high levels of problem solving, or ( 4) a high degree of change. Findings indicated that higher scores on the SDLRS were related to higher levels of job performance for all four types of job.…”
Section: Criticism Of the Field: Uniform Samplesmentioning
confidence: 99%
“…The knowledge we have regarding SDL stems primarily from the adult education literature; and while it has been suggested that the principles of SDL may be applied to the work setting (Guglielmino, Guglielmino, & Long, 1987), such assertions remain largely untested. Most research has focused on academic settings, particularly graduate school programs.…”
mentioning
confidence: 99%
“…Menurut Guglielmino & Guglielmino (2006) siswa yang memiliki self direction in learning adalah siswa yang dapat mengambil inisiatif (baik dengan atau tanpa bantuan orang lain) dalam mendiagnosis kebutuhan kebutuhan belajar mereka, merumuskan tujuan-tujuan belajar, menentukan sumbersumber belajar, memilih dan melaksanakan strategi belajar yang sesuai, dan mengevaluasi hasil belajar mereka sendiri. Siswa yang memiliki self direction in learning yang tinggi digambarkan sebagai orang yang mampu mengontrol proses belajar, mempergunakan bermacam-macam sumber belajar, mempunyai motivasi internal dan memiliki kemampuan mengatur waktu serta memiliki konsep diri yang positif dibandingkan dengan mereka yang self direction in learning-nya rendah.…”
unclassified